Pembelajaran Direct Instruction Berbasis Animasi Terhadap Konsepsi Siswa Materi Ikatan Kimia Kelas X Sman 1 Dondo Kabupaten Tolitoli - Uswatun Hasanah; Daud K Walanda; Siang Tandi Gonggo (Mitra Sains, 2017)
Uncomplete assessing of materials abstract in learning of chemistry will lead to students on experiencing misconceptions as a result of the wrong internalization. This study aimed to analyze the positive effect and significance of the direct instruction learning based on animation to wards students’ conceptions of chemical bonding in the Grade X at SMAN 1 Dondo Tolitoli. This study applied a quasi-experimental method with one group pretest-posttest design. Samples were 29 students determined by purposive sampling. The independent variable in this studywas the direct instruction learning, while the dependent variable was the students' conceptions. The data acquisition instrument was in the form of a diagnostic test consisted of 20 multiple-choice questions and reasons using Certainty of Response Index (CRI). Data was analyzed using t-test two sample pairs. Hypothesis test results obtained –taccount (-16.37) <-ttable (-2.05) at significance level of 5%. This study concluded that there is a significant effect positively of direct instruction learning based onanimation to improvestudents’ conceptions in the Grade X at SMAN 1 Dondo Tolitoli, with the effect size d = 2.8 or with a relatively large level of effectiveness.